Safe in the family - Visontai-Szabó, Katalin (European Integration Studies, 2023)
Corporal punishment of children has been a part of everyday life for centuries, as it has long been seen as a means of education. However, in the last century many social scientists, psychologists and doctors warned parents about the dangers of punitive discipline. The concept of child abuse has long been recognised in the paediatric literature, with the term “Battered Child Syndrome” being coined by Henry Kemp. Many parents see corporal punishment of their children as an effective, socially acceptable method of child-rearing. Parents hit their children not because they want to do so or because they want to hurt them, but rather because they believe that corporal punishment teaches their children positive patterns of behaviour and protects them from various threats. Parents often know of no other way to express their dissatisfaction with their child or their own helplessness. They seldom think about how their child might feel when he or she gets a beating or is waiting for the inevitable slap. The public opinion is that corporal punishment is a necessary part of discipline and education. It is from spanking and slapping that children learn to respect their parents. To improve the situation of physically abused children, it is necessary to change social attitudes towards such behaviours and to teach parents the negative effects of these behaviours. Another key task is to educate parents about alternative child-rearing methods. Corporal punishment as a means of disciplining children will not immediately disappear from parents' child-rearing repertoires. In fact, as research and expert opinion confirms, constant and consistent educational work will only lead to a gradual change in parents' attitudes and behaviour.